DESAIN INSTRUMEN LITERASI SOSIAL BUDAYA PADA MATERI KERAGAMAN SOSIAL BUDAYA BAGI PESERTA DIDIK MTs - Ika Ariyanti, Desti; Handoyo, Eko; Setiawan, Deni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The aim of this research is to design a social and cultural literacy instrument for materials on social and cultural diversity for MTs students. The method of this research is Research and Development (R&D) using a model called ADDIE. This study involved seventh-grade students of MTs Negeri 2 Kota Cirebon as subjects. The validation results from subject matter experts obtained a score of 92,8% and language expert obtained a score of 88%, confirming that this instrumen is “very feasible”. Empiricaly validity shows that 25 of the 30 questions are valid with a very high level of reliability (Cronbach’s Alpha = 0,917). The characteristics of the questions were dominated by a “medium” level of difficulty and “good” discriminating power. The instrument was also proven to be effective in improving students’ socio-cultural literacy, as shown by an increase in the average score from 60.5 to 87 and an n-gain score of 0.7003 in the “high” category. The significant difference between the pretest and posttest results was confirmed by the Wilcoxon Signed Rank Test. The students’ responses fell into the “very effective” category, confirming that the instrument was easy to understand, interesting, and relevant, making it suitable and effective for use by MTs students.